Group counseling : strategies and skills - Jacobs, Edward E. (Cengage, 2016)
GROUP COUNSELING: STRATEGIES AND SKILLS, Eighth Edition, provides an in-depth look at group counseling with an emphasis on practical knowledge and techniques for effective group leadership. The authors discuss the many facets of group counseling and provide examples of how each skill can be applied in a wide range of group settings to produce effective and efficient group sessions. The book focuses on the skills necessary for starting and ending a session, as well as on how to make the middle phase productive and meaningful. Its practical, active approach is supported by nearly 50 video segments-including several new ones-that demonstrate specific skills as well as the integration of multiple skills and techniques. Through its integration of traditional theories and concepts of group process with thoughtful strategies and specific skills, this reader-friendly book and video clips meet the needs of practicing or future counselors, social workers, psychologists, and others who are leading or preparing to lead groups in a variety of settings.